The effects of proficiency and textual enhancement technique on noticing. (February 2021) - Lee, Bradford J.
Abstract: Textual enhancement (TE) refers to manipulation of a text to make specific linguistic targets more perceptually salient. Typically, the purpose of TE is to implicitly draw learners' attention to target forms, as it has been postulated that noticing the gap between one's interlanguage and the target is a first step towards acquisition (Smith, 1991, 1993). This study investigated the effects of two forms of TE on the acquisition of the English third-person singular / s/ and / es/ forms among 382 Japanese university students. Two grammaticality judgement tasks in a pre/posttest design indicated small, but significant, increases among the two experimental groups compared to a comparison group (unenhanced text), and a control group (no treatment). The relative effect of language proficiency was also examined, with students of lower proficiency in each experimental group showing greater improvement over their control groups than their counterparts of higher proficiency. Post-interviews revealed that participants generally had not been successful at noticing the target form, and that they were predominately engaged in processing the readings for content, not form. Overall results suggest that TE is slightly effective, but it is argued that its effects may be enhanced by combining it with training students in effective learning strategies.